Pendidikan di Abad 21 HOTS (Higher Order Thingking Skills) dalam Litetasi Matematika - Mega Achdisty Noordyan; Deddy Sofyan; Iyam Maryati; Teni Sritresna; Dian Mardiani; Basuki Basuki; Cici Nurulhaq (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
“Pengabdian Kepada Masyarakat” is one of the higher education tridharma that must be implemented by higher education functional institutions by involving lecturers both individually and in groups. The purpose of this Community Service activity is as a means of delivering information in the fields of Science, Technology and Arts (IPTEKS), findings from research, creation, development and dissemination of science and technology based on current educational developments. This study aims to identify the level of knowledge and practice in the implementation of higher order skills or Higher Order Thingking Skills (HOTS) to improve mathematical literacy. The quantitative approach uses Pearson's correlation to see the closeness of the relationship between the Higher Order Thingking Skills (HOTS) ability of mathematics literacy